Clinical and Molecular Analysis of Four Patients With 11β-Hydroxylase Deficiency - Zhou, Qiaoli; Wang, Dandan; Wang, Chunli; Zheng, Bixia; Liu, Qianqi; Zhu, Ziyang; Jia, Zhanjun; Gu, Wei (Frontiers in Pediatrics, 2020)
Objective: 11β-hydroxylase deficiency (11βOHD) is a rare autosomal recessive disorder caused by mutations in the CYP11B1 gene. It is characterized by virilization, hypertension and significant final height impairment. In this study, we aim to investigate the clinical and molecular characteristics of four unrelated Chinese patients with 11βOHD disorder. Methods: The clinical information of four 11βOHD patients were carefully reviewed. Genetic analysis was performed using next-generation sequencing (NGS) based panel analysis. NGS coverage depth was analyzed to detect exonic copy-number variants (CNVs) on patient 1. Quantitative PCR (qPCR) was subsequently performed to confirm the CNVs detected from the NGS coverage depth analysis. Results: The mean age of the patients at diagnosis was 4.7 years (range, 2.0-9.3 years). Two genetically female patients (patients 1 and 2) with 11βOHD presented severe virilization of external genitalia and were raised as males. Two genetically male patients (patients 3 and 4) presented precocious puberty. Additionally, patients 1, 3 and 4 presented with hypertension. In patient 4, unilateral adrenal mass was detected and removed at the age of 9 years. Interestingly, the height of patient 4 (174.4cm, +6.7 SD) wasn’t impaired and reached his mid-parental height (173 cm). Three novel variants in the CYP11B1 gene (c.1150_1153del, c.217C>T and c.400G>C) were identified by NGS. Various bioinformatics tools revealed potential pathogenic effects for the novel variants, and evolutionary-conservation revealed that the novel missense variant affected an amino acid that is highly conserved among species. Furthermore, NGS coverage depth analysis and qPCR identified a novel heterozygous deletion of exons 1-6 in patient 1. Conclusion: Our study expands the spectrum of mutations of the CYP11B1 gene in Chinese population. In addition, We reported the first case of a patient with classical 11βOHD disorder, whose final height wasn’t compromised.